PENERAPAN E-LKPD INTERAKTIF BERBASIS PBL PADA PEMBELAJARAN FISIKA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PADA KELAS X SMA KARTIKA IV-3 SURABAYA - Burnama, Nindy Carmelia; Hariyono, Eko (Universitas Negeri Surabaya, 2024)
This study aims to describe the improvement in students' critical thinking skills after the implementation of interactive e-Worksheets (e-LKPD) with the Problem-Based Learning (PBL) model in physics education, as well as the students' responses to it on the topic of alternative energy in the 10th grade at Kartika IV-3 Senior High School in Surabaya. The research design used a nonequivalent-control group with two classes: the experimental class (X-B) and the control class (X-A). The instruments used included a critical thinking skills test and a student response questionnaire. The results of the pretest and posttest showed improvements in all aspects of critical thinking competence. Competency 4 experienced the highest increase, with pretest scores of 68 and 52.53, and posttest scores of 86.67 and 68.26. Competency 2 experienced the lowest increase, with pretest scores of 60.89 and 58.89, and posttest scores of 78.88 and 66.67. The average n-gain for class XB (experimental) was 0.593 and for class X-A (control) was 0.329, both in the medium category. The PBL model with e-LKPD had a significant impact on critical thinking skills, with a Cohen's d value of 5.414 indicating that the post-test scores distribution of the experimental group did not completely overlap with the control group.